Language Learner Autonomy: The Beliefs of English Language Students - Istanti Hermagustiana; Dian Anggriyani (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2019)
ABSTRACTThis study aims at investigating: (1) levels of autonomous learning from three groups of students with different periods of study, (2) EFL students’ beliefs towards learner autonomy and their lecturers’ roles in promoting learner autonomy. The participants of this study were three groups of EFL students at English Department in their second, fourth, and sixth semesters. The data were obtained through questionnaire surveying Autonomous Learning Scale to find out the students’ levels of autonomy and interview to figure out their beliefs about learner autonomy and the roles of lecturers to promote autonomous learning. This study revealed that all group of students were classified as being in the mediate level of autonomy. From the interviews conducted to nine participants representing each group, it was found that to become autonomous, learners need to develop the ability to evaluate their own learning. Moreover, out-of-class activities were believed to enhance learner autonomy since the activities will provide students with self-responsibility to manage the tasks. Last, in terms of the lecturers’ roles in the classroom, most participants perceived that the lecturers still had a dominant role in controlling teaching and learning, particularly in the classroom context. This dominant role eventually led students to become less autonomous circumstances, both inside and outside classrooms.ABSTRAKPenelitian ini bertujuan untuk mengetahui: (1) tingkat pembelajaran mandiri dari tiga kelompok mahasiswa Bahasa Inggris dengan periode studi yang berbeda, dan (2) keyakinan mahasiswa Bahasa Inggris terhadap pembelajaran mandiri dan peran para dosen pengajar dalam mendukung pembelajaran mandiri di kelas. Para partisipan penelitian ini adalah tiga kelompok mahasiswa yang belajar di Jurusan Pendidikan Bahasa Inggris di semester kedua, keempat, dan keenam. Data diperoleh melalui angket survei Autonomous Learning Scale untuk mengetahui tingkat pembelajaran mandiri mahasiswa dan melalui wawancara untuk mengetahui pandangan mereka tentang pembelajaran mandiri dan peran dosen pengajar untuk mempromosikan pembelajaran mandiri. Hasil yang didapat dari penelitian ini adalah bahwa semua kelompok siswa dari tiga periode studi yang berbeda diklasifikasikan dalam pembelajaran mandiri tingkat menengah. Dari wawancara yang dilakukan kepada sembilan peserta yang mewakili setiap kelompok, diketahui bahwa untuk menjadi mandiri, mahasiswa perlu mengembangkan kemampuan untuk mengevaluasi pembelajaran mereka sendiri. Selain itu, kegiatan di luar kelas diyakini dapat meningkatkan pembelajaran mandiri karena kegiatan tersebut akan mengembangkan tanggung jawab dalam mengelola tugas. Begitu pun dalam hal peran dosen di ruang kelas, sebagian besar mahasiswa merasa bahwa dosen masih memiliki peran dominan dalam mengendalikan proses belajar mengajar, terutama di dalam kelas. Peran dominan dosen ini pada akhirnya menyebabkan mahasiswa menjadi kurang mandiri baik di dalam maupun di luar kelas.How to Cite: Hermagustiana, I., Anggriyani, D. (2019). Language Learner Autonomy: The Beliefs of English Language Students. IJEE (Indonesian Journal of English Education), 6(2), 133-142. doi:10.15408/ijee.v6i2.15467